Correlation between the individual’s experience of well-being and social evaluation - Danylchenko, Tetiana (Journal of Education Culture and Society, 2021)
Aim. The aim of this paper is to define the correlation between social evaluation and personal well-being. Methods. The study involved the citizens of Chernihiv (average age – 31.5 years old): 91 people in total, 37 men and 54 women. The following methods were used: the scale of satisfaction with life scale by Diener, as adapted by Leontiev and Osin (2008); questionnaire of parameters of subjective social well-being by Danylchenko (2015); subjective life satisfaction scale by Lybyna (2008), questionnaire on the peculiarities of evaluation by other people by Danylchenko (2019). Results and conclusion. In Ukrainian society, the most important reference groups are parents and a spouse, while friends and colleagues play a comparatively smaller role. All these groups are more likely to give positive and neutral social evaluations. However, negative evaluations are more likely to come from colleagues and friends, and positive – from family. There are differences in indicators of subjective well-being, social acceptance (as a measure of social well-being) and competence between people who are assessed predominantly positively and predominantly negatively. Subjective well-being is reduced reproaches from reference groups. Praise contributes to the enhancement of subjective social well-being Comparison with other people and the existence of a role model reduces psychological well-being. The filter for the perception of positive and negative evaluations from the social environment is a person’s self-acceptance.